The impact of individual trauma symptoms of deployed soldiers on relationship satisfaction - Goff, Briana S. Nelson; Crow, Janet R.; Reisbig, Allison M.J.; Hamilton, Stacy (My University, 2007)
Research traditionally has focused on the development of individual symptoms in those who experienced trauma directly but has overlooked the interpersonal impact of trauma. The current study reports data from 45 male Army soldiers who recently returned from a military deployment to Iraq (Operation Iraqi Freedom) or Afghanistan (Operation Enduring Freedom)and their female spouses/partners. The results indicated that increased trauma symptoms, particularly sleep problems, dissociation, and severe sexual problems, in the soldiers significantly predicted lower marital/relationship satisfaction for both soldiers and their female partners. The results suggest that individual trauma symptoms negatively impact relationship satisfaction in military couples in which the husband has been exposed to war trauma.
Keywords: Military deployments; Traumatic stress; Operation Iraqi Freedom; Couples